Adaptive laboratory evolution of Salmonella enterica in acid stress - Ghoshal, Mrinalini; Bechtel, Tyler D.; Gibbons, John G.; McLandsborough, Lynne (Frontiers in Microbiology, 2023)
Introduction Adaptive laboratory evolution (ALE) studies play a crucial role in understanding the adaptation and evolution of different bacterial species. In this study, we have investigated the adaptation and evolution of Salmonella enterica serovar Enteritidis to acetic acid using ALE. Materials and methods Acetic acid concentrations below the minimum inhibitory concentration (sub-MIC) were used. Four evolutionary lineages (EL), namely, EL1, EL2, EL3, and EL4, of S. Enteritidis were developed, each demonstrating varying levels of resistance to acetic acid. Results The acetic acid MIC of EL1 remained constant at 27 mM throughout 70 days, while the MIC of EL2, EL3, and EL4 increased throughout the 70 days. EL4 was adapted to the highest concentration of acetic acid (30 mM) and demonstrated the highest increase in its MIC against acetic acid throughout the study, reaching an MIC of 35 mM on day 70. The growth rates of the evolved lineages increased over time and were dependent on the concentration of acetic acid used during the evolutionary process. EL4 had the greatest increase in growth rate, reaching 0.33 (h−1) after 70 days in the presence of 30 mM acetic acid as compared to EL1, which had a growth rate of 0.2 (h−1) after 70 days with no exposure to acetic acid. Long-term exposure to acetic acid led to an increased MIC of human antibiotics such as ciprofloxacin and meropenem against the S. enterica evolutionary lineages. The MIC of ciprofloxacin for EL1 stayed constant at 0.016 throughout the 70 days while that of EL4 increased to 0.047. Bacterial whole genome sequencing revealed single-nucleotide polymorphisms in the ELs in various genes known to be involved in S. enterica virulence, pathogenesis, and stress response including phoP, phoQ, and fhuA. We also observed genome deletions in some of the ELs as compared to the wild-type S. Enteritidis which may have contributed to the bacterial acid adaptation. Discussion This study highlights the potential for bacterial adaptation and evolution under environmental stress and underscores the importance of understanding the development of cross resistance to antibiotics in S. enterica populations. This study serves to enhance our understanding of the pathogenicity and survival strategies of S. enterica under acetic acid stress.